Use of thiopurines and risk of colorectal neoplasia in patients with inflammatory bowel diseases: a meta-analysis. - Jianfeng Gong (Public Library of Science (PLoS), 2013)
Objective Inflammatory bowel disease (IBD) is commonly treated with thiopurines such as azathioprine and mercaptopurine for the maintenance of remission. Studies examining chemopreventive of these medications on colorectal neoplasm in IBD patients have yielded conflicting results. We performed a meta-analysis to assess the role of thiopurines for this indication. Methods We performed a systematic search of PubMed, Web of Science, EMBASE and Cochrane to identify studies reporting colorectal neoplasm from IBD patients treated with thiopurines and conducted a meta-analysis of pooled relative risk (RR) using the random effects model. Results Nine case-control and ten cohort studies fulfilled the inclusion criteria. The use of thiopurines was associated with a statistically significant decreased incidence of colorectal neoplasm (summary RR=0.71, 95% CI=0.54-0.94, p=0.017), even after adjustment for duration and extent of the disease, but there was high heterogeneity among studies (I(2)=68.0%, p<0.001). The RR of advanced neoplasm (high-grade dysplasia and cancer) was 0.72 (95%CI=0.50-1.03, p=0.070) and that of cancer was 0.70 (95% CI=0.46-1.09, p=0.111) for thiopurine-treated patients. Heterogeneity of the studies was affected by the sample size (</≥ 100 cases) and whether the patients had longstanding colitis (≥ 7 years). Conclusion The current meta-analysis revealed that thiopurines had a chemopreventive effect of colorectal neoplasms and a tendency of reducing advanced colorectal neoplasms in IBD. Due to the heterogeneity of included studies, these results should be interpreted with caution.